Rendering Trauma Beneficial… for Whom? Gregory of Nyssa’s Homily 12 on the Song of Songs - Dasios, Maria (Vox Patrum, 2024)
Gregory’s Homily 12 on the Song of Songs offers one opportunity to trace the legacies of the compelling claim, in Galatians 6:17, that Paul bears “the marks of Christ” on his body. Gregory appeals to this verse to aid his exegesis of Song 5:7 (a violent passage he calls “repellant in its plain sense”) and develop his claims that “the wound”, after all, is “an admirable thing”. My paper probes social and ethical dimensions of this exegetical and cultural conceptual lineage. It surveys wounds and marks in Homily 12; suggests how other works by Gregory support “striking and wounding” as enacting spiritual healing (ἴασιν); considers contexts for violence in the name of guardianship and instruction in late antiquity; and closes by considering violence enacted in the name of Christianization and “civilization” in Canada’s residential schools. This study embeds Gregory’s treatment of Gal 6:17 in a larger attempt to raise critical questions about the persistence of benevolent understandings of trauma and violence across diverse Christian exegetical contexts and the harms such understandings may perpetuate.